Implementasi Analytical Hierarchy Process Dan Metode Perbandingan Eksponensial Untuk Pemberian Reward Karyawan - Suharsono Bantun; Rabiah Adawiyah; Kharis Syaban; Dimas Febriyan Priambodo; Nirsal Nirsal; Suci Pricilia Lestari; Jayanti Yusmah Sari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Giving employee rewards for a company is one of the agendas that must be considered carefully. This is because the provision of rewards can be an indicator to encourage employees to work harder for more optimal company performance, but in reality it is difficult to determine employees who deserve to receive rewards because many employees are entitled to receive rewards but the quota is limited. This is the difficulty faced by PT. YZZ especially in providing annual rewards, because in the calculation process it has 5 assessment criteria so that in this case a decision support system is needed to assist managers in providing recommendations for employees who are entitled to receive rewards using the Analytical Hierarchy Process (AHP) and Metode Perbandingan Eksponensial (MPES). Based on the results of the study, there are several alternatives that are recommended to receive rewards so that it can be suggested in giving employee rewards.